2019
DOI: 10.1111/cdoe.12514
|View full text |Cite
|
Sign up to set email alerts
|

Does competition affect the clinical decision‐making of dentists? A geospatial analysis

Abstract: Objectives To investigate the association between dentists' geographic density and perceptions of market competition with clinical decision‐making among a representative sample of dentists in Ontario, Canada's most populated province. Methods Competition was quantified using dentist density, defined as the number of dental clinics lying within a one kilometre radius around the respondents' clinic address and by self‐reported perceived pressure from other dental clinics. The outcome (clinical decision‐making or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In Korea, physicians and dentists are remunerated based on fee‐for‐services, and the number of practicing dentists per 100,000 individuals has continued to rise from 0.31 in 2000 to 0.49 in 2017 20 . Fee‐for‐service tends to increase the volume of medical services than the salary system, 21,22 and an increase in physician density tends to lead to physician‐induced demand 23‐26 . These factors may be responsible for the increase in volume of dental treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, physicians and dentists are remunerated based on fee‐for‐services, and the number of practicing dentists per 100,000 individuals has continued to rise from 0.31 in 2000 to 0.49 in 2017 20 . Fee‐for‐service tends to increase the volume of medical services than the salary system, 21,22 and an increase in physician density tends to lead to physician‐induced demand 23‐26 . These factors may be responsible for the increase in volume of dental treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The data for this study came from a larger study, which employed a 46‐item survey with questions based on factors that the literature suggests has a relationship to treatment decision‐making . It included questions on demographic characteristics, such as age and gender of the dentist; practice characteristics, such as age of the practice and number of hygienists employed; and professional characteristics, such as opinions on professional responsibilities.…”
Section: Methodsmentioning
confidence: 99%
“…The data for this study came from a larger study, which employed a 46-item survey with questions based on factors that the literature suggests has a relationship to treatment decision-making. 17,18 It included questions on demographic characteristics, such as age and gender of the dentist; practice characteristics, such as age of the practice and number of hygienists employed; and professional characteristics, such as opinions on professional responsibilities. There were also questions to assess dentists' perceptions about personal and market pressures, such as the size of student and practice loans and satisfaction with the level of busyness in their dental practices.…”
Section: Survey Creationmentioning
confidence: 99%
“…Dentists located in regions with competitive pressure from other dentists presented an odds 63% higher to indicate a more aggressive approach than dentists located in medium competitive regions. Also, the dentist in very low competitive areas presented an odds 31% higher to indicate aggressive dentistry treatments when compared with medium density regions 28 . Therefore, considering the Brazilian and Guatemalan distribution of dental schools and Dentists we found some differences that could help us.…”
Section: Discussionmentioning
confidence: 96%
“…Some patient's characteristics could influence the decision making of health professionals [25][26][27] . Moreover, it was observed that competition affected the clinical decision-making of dentists in Canada 28 . Dentists located in regions with competitive pressure from other dentists presented an odds 63% higher to indicate a more aggressive approach than dentists located in medium competitive regions.…”
Section: Discussionmentioning
confidence: 99%